Migration-Led Institutional Change in Urban Development and Planning - Robert Barbarino (Urban Planning, 2021)
The migration-city-nexus has become central in migration and urban studies alike. This ‘local turn’ has not only initiated a rethinking of the local level as an independent level of migration policy-making but also broadened the discourse on how migration processes actually change cities. Therefore, the thematic issue at hand seeks to understand how migration-led development processes in cities promote and shape institutional change, and which actors transform policies, structures, and discourses on migration in different settings. It questions how migration-related issues in urban development are being handled and transformed by local state and civil society actors. With 11 empirical articles on local negotiations of migration in urban development in different settings, this thematic issue applies an institutional change perspective on local migration policy-making to contribute to a broader understanding of migration-led development in both urban and migration studies. When it comes to clearly capturing migration-led institutional change in urban development and planning, the contributions demonstrate great heterogeneity. They reveal that research on migration-led institutional change still has many biases and is very dependent on theoretical perspectives, positionalities of researchers, and the local context of the case studies.